AN ANALYSIS OF STUDENTS’ ENGLISH SPEAKING ANXIETY IN LEARNING NARRATIVE TEXT THROUGH ONLINE LEARNING AT GRADE X MAN 1 INDRAGIRI HILIR - Felci Tria Sauhana; Sri Erma Purwanti; Siti Zakiyah Drajat (Fakultas Keguruan dan Ilmu Pendidikan, 2023)
Speaking anxiety was the main problem in this research. Students found it was difficult in pronouncing or spelling the words and they were afraid of making mistakes in speaking English. This research was aimed to find out the level of students' English speaking anxiety in learning narrative text through online learning. This research was conducted at MAN 1 Indragiri Hilir, Tembilahan. The particiants of this research were the students at grade XI IPA 2 MAN 1 Indragiri Hilir which consists of 34 students. Sampling was done by using purposive sampling technique. This research used a quantitative descriptive method and distributed questionnaires to collect the data. Based on the result of the research, there were 7 indicators of speaking anxiety. They were being blank, forgetting the words they have read, unable to say what they know, less interested in the learning process, silent, afraid of miscommunication, and avoid talking. Based on this analysis, it was concluded that the result of this research indicated that